Research of Bar Optimization for the High Speed Delta Robot - Zheng Kunming; Zhang Qiuju (Jixie chuandong)
In order to give full play of the advantages of error accumulated small and fast running speed of the high speed Delta robot,the research of bar optimization for the Delta robot is need. Based on establishing the kinematics and dynamics of rigid body model of the system,the global dexterity and the shock vibration function of driving arm are defined,according to the actual work requirements of the Delta robot,the work trajectory is planned. By using MATLAB genetic algorithm toolbox,respectively with dexterity and shock and vibration function as fitness function,the optimal solution of global is got. Then,taking the obtained optimal solution as the upper and lower bounds,by using the weight factor transformation method,the multi- objective optimization of dexterity and shock vibration function is transformed into a single objective optimization,then according to the above method,a set of meet the scale parameter optimization objectives are synthesized,a reference for the Delta robot structure optimization design is provided.